SMALL BUSINESS SUPPORT POLICY IN LATVIA - Šneidere, Ruta; Būmane, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Economic growth is the important factor for improving competitiveness and to ensure the availability of financial resources at all stages of business development. The authors explore European Union activities to promote the development of small and medium enterprises, the Latvian business environment, the regulatory framework, the accounting regulatory framework for small and medium enterprises. The research study included an assessment of the business environment in the international context for the years 2010 – 2016, national support programmes providing financial resources, their availability and tax policy guidelines for small and medium enterprises. The research study results are summarized in a number of conclusions, and recommendations have been developed. Research methodology is based on the analysis of laws and regulations, statistical data and economic and scientific literature studies.